Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Research Approaches on Workplace Learning
The volume comprises a variety of research approaches that seek to explore and understand employees’ learning and development through and for work. Working life reveals challenges through technological, economic and societal development that can only rudimentarily be addressed by formal education and training. Workplace learning becomes more and more important for employees and enterprises to successfully cope with these challenges. Workplace learning is a steadily growing field of educational research but it lacks so far a scholastic canon – there is rather a diversity of research approaches. This volume reflects this diversity by bringing together researchers from different countries and different theoretical backgrounds, presenting their current research on topics that all are relevant for understanding presages, processes and outcomes of workplace learning. Hence, this volume is of relevance for researchers as well as practitioners in the field and policy makers.
Keywords: tivesTeam learningTeam climateSocial influences on team learningKnowledge construction in teamsLearning cultureAcknowledgement of competencesTechnology and professional learningCreation of a learning eco-systemDiversity as a challenge for organisationsHigher education as preparation for WPLSocial support in networks and professional learningvocational and professional education

Research on Workplace Learning in Times of Digitalisation - Harteis, Christian (Research Approaches on Workplace Learning)
The article explores the particular quality of changes introduced through the latest wave of digital transformation of workplaces. It has effects on workflow processes, on distribution of work and tasks, and the mode of distributing working tasks, e.g. through cyber-physical systems. Hence, the changes in work are manifold and require changes in vocational education and training as well as in workplace learning. These changes reveal new challenges for research on workplace learning. Finally, conclusions for future workplace learning research will be developed.
Keywords: Digitalisation Self organisation Distribution of labour Automation

Digitalization of work: Challenges for workplace learning - Harteis, Christian; Goller, Michael; Gerholz, Karl-Heinz (The SAGE Handbook of Learning and Work)
The digitalization of workplaces can introduce changes on various levels of work activities. Educational research follows this transformation in one of two ways: On the one hand, there is the optimistic perspective of expecting to improve the quality of work and work life; on the other hand, there is the expectation that conditions of work and work life will generally deteriorate. Irrespective of the concrete outcomes of digitalization, a general agreement exists that digitalization will induce changes at workplaces that affect individuals and the tasks they do. At the same time, however, scholars disagree as to whether employees experience these changes in terms of affordances that engage them into learning new processes or if they experience constraints that inhibit further engagement in learning. This chapter explores the particular developments covered under the topic of digitalization at and of work, explains particular challenges of the introduction of cyber-physical systems and analyzes consequences for workplace learning. It focuses on conceptual change as a theoretical framework for understanding the quality of learning processes that seem inevitable in order to cope with the new requirements and – more importantly – to use the potentials of the new technologies. It then sketches the poor state of empirical research conducted in this area – so far limited to exploratory field studies – even in times of corona, which has boosted the digital transformation. The chapter ends with a description of the potential and problems of – at best interdisciplinary – research into learning at digitalized workplaces.

Delphi-Technique as a Method for Research on Professional Learning - Harteis, Christian (Methods for Researching Professional Learning and Development)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. Eine explorative Studie - Caruso, Carina; Neuweg, Georg Hans; Wagner, Marlene; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Erkenntnisse zur Verbesserung von Mentoringprozessen in der Lehrer:innenausbildung - Goller, Michael; Caruso, Carina; Harteis, Christian (SEMINAR – Lehrerbildung und Schule)

The concept of a digital twin and its potential for learning organizations - Berisha-Gawlowski, Angelina; Caruso, Carina; Harteis, Christian (Digital transformation of learning organizations)

Die Forderung nach Lebenslangem Lernen: Zwischen Banalität, Herausforderung und Zumutung - Harteis, Christian (Lebenslanges Lernen in der Musikpädagogik. Theorie und Praxis)

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years.Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Education

Digitalisation in agriculture: Knowledge and learning requirements of German diary farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal of Research on Vocational and Educational Training)

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

Theorie und Praxis in der Lehrerbildung

Fachdidaktische Ansätze der Theorie-Praxis-Relationierung - Caruso, Carina; Harteis, Christian; Gröschner, Alexander (Theorie und Praxis in der Lehrerbildung: Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)
Der Beitrag konstituiert sich als Zusammenschau von Perspektiven der Beiträge, die in diesem Sammelband enthalten sind. Es werden dabei Kerninhalte wie zentrale Fragen, Gestaltungsansätze und Perspektiven der Beiträge gebündelt, wobei die einzelnen fachdidaktischen Akzentuierungen in Bezug auf das Verständnis der Theorie-Praxis-Relationierung sowie fachspezifische Impulse zur Gestaltung der Lernbegleitung nicht wiederholt werden. Vielmehr zielt der Beitrag darauf ab, ausgewählte Aspekte zusammenzuführen und kritisch zu diskutieren, um Akzentuierungen in den fachdidaktischen Perspektiven hervorzuheben. Um diesem Vorhaben Rechnung zu tragen, gliedert sich dieses Resümee entlang der fachspezifischen Besonderheiten und Gemeinsamkeiten, die in den voranstehenden Beiträgen zur Geltung kommen. Im Rahmen einer abschließenden Diskussion werden Fragen hinsichtlich der zukünftigen Theorie-Praxis-Relationierung aufgeführt, deren Beantwortung als Aufgabe der Lehrerbildung bestehen bleibt.
Keywords: Fachdidaktik; Lehrerbildung; Professionalisierung; Theorie-Praxis-Relationierung

Praxisphasen in der Lehrerbildung - Caruso, Carina; Harteis, Christian; Gröschner, Alexander (Theorie und Praxis in der Lehrerbildung Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)
Die Ausweitung schulpraktischer Anteile bzw. die Integration von Langzeitpraktika kennzeichnet die universitäre Lehrerbildung in Deutschland. Mit dieser Ausweitung bzw. Integration ist der Anspruch verbunden, dass schulpraktische Anteile im Studium die professionelle Entwicklung angehender Lehrpersonen positiv beeinflussen.

The Concept of a Digital Twin and Its Potential for Learning Organizations - Berisha-Gawlowski, Angelina; Caruso, Carina; Harteis, Christian (Digital Transformation of Learning Organizations)
The digital transformation of organizations in the industrial sector is primarily driven by the opportunity to increase productivity while simultaneously reducing costs through integration into a cyber-physical system. One way to fully tap the potential of a cyber-physical system is the concept of the digital twin, i.e., the real-time digital representation of machines and resources involved – including human resources. The vision of representing humans by digital twins primarily aims at increasing economic benefits. The digital twin of a human, however, cannot be designed in a similar way to that of a machine. The human digital twin shall rather enable humans to act within the cyber-physical system. It therefore offers humans a power of control and the opportunity to provide feedback. The concept of the digital twin is still in its infancy and raises many questions in particular from an educational perspective. The contribution aims at answering the following questions and refers to the example of team learning: Which and how much data should and may the digital twin contain in order to support humans in their learning? To what extent will humans be able to control and design their own learning? How may skills, experiences, and social interactions of humans be represented in the digital twin; their growth and further development, respectively? With cyber-physical systems transcending corporate, national, and legal boundaries, what learning culture will be the frame of reference for the involved organizations?
Keywords: Digital twin; Learning organization; Change; Team learning; Professional development

Expertiseentwicklung: Umwandlung von Wissen in Können - Harteis, Christian; Billett, Stephen; Gruber, Hans (Implizites Wissen. Berufs- und wirtschaftspädagogische Annäherungen)

Inwiefern können Praxisphasen im Studium zu einer Theorie-Praxis-Relationierung beitragen? Implikationen für die professionelle Entwicklung angehender Lehrkräfte. - Harteis, Christian; Caruso, Carina (Verlängerte Praxisphasen in der universitären Lehrerbildung: Spannungsfelder zwischen Theorie, Praxis und der Bestimmung von Professionalisierung)

Digitalisierung in der Landwirtschaft. Gründe, Optionen und Bewertungen aus Perspektive von Milchviehlandwirtinnen und -landwirten - Goller, Michael; Caruso, Carina; Berisha-Gawlowski, Angelina; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Berufliche Förderung in Zeiten von Digitalisierung und Berufsbildung 4.0 war ein Schwerpunktthema der Hochschultage Berufliche Bildung 2019 in Siegen. Die Beiträge des Sammelbandes geben einen Überblick über die diskutierten Konzepte und Handlungsansätze. Der erste Teil befasst sich mit Fragen zum digitalen Kompetenzerwerb in verschiedenen Arbeitsdomänen, von den Auswirkungen der Digitalisierung auf industrieller Arbeit und Landwirtschaft bis zur Entwicklung von Medienkompetenz als Aufgabe der Berufsbildung. Im zweiten Teil stehen Fragen zur beruflichen Förderung in Zeiten der Digitalisierung im Mittelpunkt. Themen sind u.a. Lernortkooperationen, digitale Transformation in der Ausbildungsvorbereitung an Berufskollegs sowie Benachteiligtenförderung in digitalen Kontexten. Der Band richtet sich an Wissenschaftler und Wissenschaftlerinnen sowie Akteure und Akteurinnen in der beruflichen Bildung, im Übergangssystem, in der beruflichen Förderung und an Berufsschulen.
Keywords: Arbeitsmarktförderung; Arbeitswelt; Arbeitswelt - Strukturwandel; Benachteiligte; Beruf; Berufliche; Bildungberufliches Lernen; Berufskolleg; Berufswahl; Didaktik; Digitale Arbeitswelt; Digitale Bildung; Digitale Kompetenzen; Digitale Lehre; Digitales Lernen; Digitalisierung; Industrie 4.0; Landwirtschaft; Lernprozess; Lernprozesse; Lernprozesse und -begleitung; Medienkompetenz; Übergangsmanagement

The contribution of mental simulation to the development of intuition - Steffen, Bianca; Goller, Michael; Harteis, Christian (Intuition handbook: Bridging research and practice)
How can intuition research inform practice? As the use of intuition in business has become more widely accepted, companies struggle to understand how to use this additional resource efficiently, while corporate trainers and university educators lack tools to develop it as a skill. This truly international Handbook provides relevant answers with: • chapters by academics and practitioners, written in a concise, digestible format to make it accessible to non-academic readers • empirical studies from multiple industry/service sectors that demonstrate an integrated use of intuition and analysis in decision making • studies from industry and education that demonstrate how to develop intuition, including a ground-breaking research in problem solving • non-Western perspectives illustrated on case studies from Japan and China • use of language protocols/methods to bring intuition into our awareness • new research into group/collective intuition (based on language analysis and quantum physics) • research related to sensing and sense making. Due to its focus on bridging theory and practice, the Handbook is of value not only to academics and organizational researchers but also to industry professionals, corporate trainers and university educators who search for answers on how to incorporate intuition into a common skill set. Accessible in style, it will also appeal to educated business readers.

Engineering students' learning during internships: Exploring the explanatory power of the job demands‐control‐support model - Goller, Michael; Harteis, Christian; Gijbels, David; Donche, Vincent (Journal of Engineering Education)

Conceptual Change in the Face of Digitalization: Challenges for Workplaces and Workplace Learning - Harteis, Christian; Goller, Michael; Caruso, Carina (Frontiers in Education)

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf: Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Keywords: Arbeitsmarktförderung; Arbeitswelt; Arbeitswelt - Strukturwandel; Benachteiligte

Auswirkungen der Digitalisierung industrieller Arbeit auf die allgemeine und berufliche Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung und Berufsbildung 4.0 am Übergang Schule - Beruf)

Conceptual Change in the Face of Digitalization - Harteis, Christian; Goller, Michael; Caruso, Carina (Frontiers in Education)
The article discusses the explanatory power of conceptual change for research on workplace learning in digitalized workplaces. Interestingly, research on conceptual change is well-established within the area of science education but widely neglected within the broad area of workplace learning research. Digitalization of work establishes new quality of tasks and tools by integrating workers and machines into digital networks. Hence, conceptual change can be considered a core concept for identifying workers’ successful adaption to digital transformation. Therefore, conceptual change research in the area of workplace learning in digitalized workplaces is highly relevant. The article reflects upon reasons, explores the potential of conceptual change for understanding workplace learning in digitalized workplaces, and illustrates the argumentation by exemplarily referring to digitalized farming. Finally, the article provides suggestions for future research.
Keywords: conceptual change; digitalization; workplace learning; professional development; agriculture

Inwiefern können Praxisphasen im Studium zu einer Theorie-Praxis- Relationierung beitragen? Implikationen für die professionelle Entwicklung angehender Lehrkräfte - Caruso, Carina; Harteis, Christian (Verlängerte Praxisphasen in der Lehrer*innenbildung Konzeptionelle und empirische Aspekte der Relationierung von Theorie und Praxis)

Digitalisierung in der Landwirtschaft: Gründe, Optionen und Bewertungen aus Perspektive von Milchviehlandwirtinnen und -landwirten - Goller, Michael; Caruso, Carina; Berisha-Gawlowski, Angelina; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
In diesem Beitrag werden Auswirkungen der Digitalisierung von Produktions- und Geschäftsprozessen (Industrie 4.0) auf die Verrichtung und Organisation von Arbeit betroffener Beschäftigter (Arbeit 4.0) thematisiert. Fokussiert wird dabei, inwiefern sich Arbeitsprozesse durch die Digitalisierung der Landwirtschaftsbetriebe verändern, wie Beschäftigte die mit der Digitalisierung verbundenen Veränderungen ihrer Arbeit erleben und welche Kompetenzen aus ihrer Perspektive benötigt werden, damit sie ihrer Tätigkeit adäquat nachkommen können. Auf Basis einer Interviewstudie mit Landwirtinnen und Landwirten, die in der Milchviehwirtschaft tätig sind, werden im folgenden Beitrag nachstehende Fragen beantwortet: Wie wird der Wechsel vom traditionellen zum digitalisierten Landwirtschaftsbetrieb von den beschäftigten Landwirten erlebt und finden sich Hinweise auf Entfremdungs- bzw. Entgren- zungstendenzen? Welche Kompetenzen benötigen die Landwirtinnen und Landwirte zur Bewältigung ihrer digitalisierten Arbeitstätigkeit im Vergleich zur traditionellen Landwirtschaft und wie wurden die nun benötigten Kompetenzen zur Bewältigung der veränderten Arbeit erworben?
Keywords: Digitale Transformation; Digitalisierung; Industrie 4.0; Arbeit 4.0; Landwirtschaft / digital transformation; digitalisation; industry 4.0; work 4.0; agriculture

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Digitalisierung ist derzeit ein viel diskutiertes Thema. Mit ihr werden derart tief grei- fende Veränderungen der Gesellschaft und Arbeitswelt erwartet, dass sie häufig als digitale Revolution bezeichnet wird. Gleichzeitig wirft die Auseinandersetzung mit diesen antizipierten Veränderungen viele noch unbeantwortete Fragen auf. Diese umfassen unter anderem Überlegungen hinsichtlich des Substitutionspotenzials menschlicher Arbeit durch die Digitalisierung, die Frage nach der Ausgestaltung der Rolle des Menschen in der Industrie 4.0 und schließlich Erwägungen in Bezug auf die Vorbereitung und Begleitung von Beschäftigten in der digitalen Transformation. Der vorliegende Beitrag gibt Aufschluss über die Dimensionen der Digitalisierung und die derzeit diskutierten Entwicklungslinien; er befasst sich weiterhin mit den sich daraus ergebenden Herausforderungen und Bedeutungen für die industrielle Arbeit und die Beschäftigten. Abschließend werden daraus abzuleitende Implikationen für die berufliche und allgemeine Bildung diskutiert.
Keywords: Digitalisierung; Industrie 4.0; Arbeit 4.0; berufliche Aus- und Weiterbildung; allgemeine Bildung / digitalization; industry 4.0; work 4.0; vocational education and training; general education

Supporting learning at work in an era of digitalization of work - Harteis, Christian (Work-based learning as a pathway to competence-based education)

Finnish and German student teachers’ motivations for choosing teaching as a career. The first application of the FIT-Choice scale in Finland - Goller, Michael; Ursin, Jani; Vähäsantanen, Katja; Festner, Dagmar; Harteis, Christian (Teaching and Teacher Education)

Die Auswirkungen der Digitalisierung auf die Bedeutung beruflicher Qualifikation aus betrieblicher Sicht - Harteis, Christian; Goller, Michael; Fischer, Christoph (Beruf, Beruflichkeit, Employability)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Wissensmanagement unter Bedingungen von Arbeit 4.0 - Harteis, Christian; Fischer, Christoph (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)
Keywords: i40; learning culture

Digitalisation of Work: Between Affordances and Constraints for Learning at Work - Fischer, Christoph; Goller, Michael; Brinkmann, Lorraine; Harteis, Christian (Digital Workplace Learning)
Keywords: i40; learning culture

Individual and social influences on professional learning. Supporting the acquisition and maintenance of expertise. - Gruber, Hans; Harteis, Christian

The impact of digitalization in the workplace: an educational view

Machines, Change and Work: An Educational View on the Digitalization of Work - Harteis, Christian (The Impact of Digitalization in the Workplace)

Developing Occupational Expertise through Everyday Work Activities and Interactions - Billett, Stephen; Harteis, Christian; Gruber, Hans (The Cambridge Handbook of Expertise and Expert Performance)

Do we betray errors beforehand? The use of eye tracking, automated face recognition and computer algorithms to analyse learning from errors. - Harteis, Christian; Fischer, Christoph; Töniges, Torben; Wrede, Britta (Frontline Learning Research)

The journey to proficiency: Exploring new objective methodologies to capture the process of learning and professional development. - Harteis, Christian; Kok, Elen; Jarodzka, Halszka (Frontline Learning Research)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Intuition as Crucial Component of Professional Competence: Its Relevance for Competence-based Vocational and Professional Education and Training - Harteis, Christian (Competence-based Vocational and Professional Education)

Emotions, coping and learning in error situations in the workplace - Rausch, Andreas; Seifried, Jürgen; Harteis, Christian (Journal of Workplace Learning)

Human agency at work: Towards a clarification and operationalisation of the concept - Goller, Michael; Harteis, Christian (Agency at Work)

Learning from errors in workplace settings - Harteis, Christian; Gartmeier, Martin (Journal of Workplace Learning)

Epistemische Überzeugungen Beschäftigter und ihre Bedeutung für berufliches Lernen - Harteis, Christian; Festner, Dagmar; Bauer, Johannes (Wissen und Lernen. Wie epistemische Überzeugungen Schule, Universität und Arbeitswelt beeinflussen)

Bildungsarbeit in Wirtschaft und Betrieb - Harteis, Christian; Heid, Helmut (Handbuch Bildungsforschung)

Die Bedeutung subjektiver Sichtweisen für die Implementierung betrieblicher Lernkultur - Fischer, Christoph; Harteis, Christian (Informelles Lernen, Annäherungen - Problemlagen - Forschungsbefunde)
Keywords: Epistemische Überzeugungen; learning culture